Predictors of in-ICU length of stay among congenital heart defect patients using artificial intelligence model: A pilot study - João Chang Junior; Luiz Fernando Caneo; Aida Luiza Ribeiro Turquetto; Luciana Patrick Amato; Elisandra Cristina Trevisan Calvo Arita; Alfredo Manoel da Silva Fernandes; Evelinda Marramon Trindade; Fábio Biscegli Jatene; Paul-Eric Dossou; Marcelo Biscegli Jatene (Heliyon, 2024)
Objective: This study aims to develop a predictive model using artificial intelligence to estimate the ICU length of stay (LOS) for Congenital Heart Defects (CHD) patients after surgery, improving care planning and resource management. Design: We analyze clinical data from 2240 CHD surgery patients to create and validate the predictive model. Twenty AI models are developed and evaluated for accuracy and reliability. Setting: The study is conducted in a Brazilian hospital's Cardiovascular Surgery Department, focusing on transplants and cardiopulmonary surgeries. Participants: Retrospective analysis is conducted on data from 2240 consecutive CHD patients undergoing surgery. Interventions: Ninety-three pre and intraoperative variables are used as ICU LOS predictors. Measurements and main results: Utilizing regression and clustering methodologies for ICU LOS (ICU Length of Stay) estimation, the Light Gradient Boosting Machine, using regression, achieved a Mean Squared Error (MSE) of 15.4, 11.8, and 15.2 days for training, testing, and unseen data. Key predictors included metrics such as “Mechanical Ventilation Duration'', “Weight on Surgery Date'', and “Vasoactive-Inotropic Score''. Meanwhile, the clustering model, Cat Boost Classifier, attained an accuracy of 0.6917 and AUC of 0.8559 with similar key predictors. Conclusions: Patients with higher ventilation times, vasoactive-inotropic scores, anoxia time, cardiopulmonary bypass time, and lower weight, height, BMI, age, hematocrit, and presurgical oxygen saturation have longer ICU stays, aligning with existing literature.